Maximizing laboratory production of aflatoxins and fumonisins for use in experimental animal feeds - Ochieng, P.E.; Kemboi, D.C.; Scippo, M.L.; Gathumbi, J.K.; Kang'ethe, Erastus K.; Doupovec, B.; Croubels, S.; Lindahl, Johanna F.; Antonissen, G.; Okoth, S. (MDPI, 2022)
Warm and humid climatic conditions coupled with poor agricultural practices in sub-Saharan Africa favor the contamination of food and feed by Aspergillus flavus and Fusarium verticillioides fungi, which subsequently may produce aflatoxins (AFs) and fumonisins (FBs), respectively. The growth of fungi and the production of mycotoxins are influenced by physical (temperature, pH, water activity, light and aeration), nutritional, and biological factors. This study aimed at optimizing the conditions for the laboratory production of large quantities of AFs and FBs for use in the animal experiments. A. flavus and F. verticillioides strains, previously isolated from maize in Kenya, were used. Levels of AFB1 and total FBs (FB1, FB2, and FB3) in different growth substrates were screened using ELISA methods. Maize kernels inoculated with three different strains of A. flavus simultaneously and incubated at 29 °C for 21 days had the highest AFB1 level of 12,550 ± 3397 μg/kg of substrate. The highest level of total FBs (386,533 ± 153,302 μg/kg of substrate) was detected in cracked maize inoculated with three different strains of F. verticillioides and incubated for 21 days at temperatures of 22–25 °C in a growth chamber fitted with yellow light. These two methods are recommended for the mass production of AFB1 and FBs for animal feeding trials.